The bridge to business evolvability: strategic agility’s mediating role for innovation and collaboration - Emmanuel P. Paulino; Menandro T. Manalo; Ronald P. Romero (Future Business Journal)
Abstract This study investigates the mediating role of Strategic Agility (SA) in the relationship between Innovation Performance (IP), Collaborative Capabilities (CC), and Business Evolvability (BE) within the hotel industry. By leveraging a survey-based design, data from 250 hotel managers in Metro Manila were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings confirm that both IP and CC significantly enhance SA, which, in turn, positively influences BE. SA partially mediates the effects of IP and CC on BE, underscoring its dual role as both an enabler of adaptability and a strategic mechanism for translating innovation and collaboration into long-term competitiveness. Beyond theoretical contributions to the Dynamic Capabilities Theory, this study offers actionable insights for hotel managers. To foster SA and enhance BE, hotel executives should prioritize investments in adaptive technologies, promote cross-functional collaboration, and cultivate an organizational culture that embraces continuous innovation and strategic responsiveness. Moreover, the results provide guidance for industries beyond hospitality—such as retail, healthcare, and financial services—where agility is crucial for sustaining business evolvability in dynamic market conditions. By highlighting the interplay of innovation, collaboration, and agility, this study provides a framework for organizations seeking to transform uncertainty into a competitive advantage.